Kinetic and finite ion mass effects on the transition to relativistic self-induced transparency in laser-driven ion acceleration. (22nd December 2017) - Siminos, E; Grech, M; Wettervik, B Svedung; Fülöp, T
Abstract: We study kinetic effects responsible for the transition to relativistic self-induced transparency in the interaction of a circularly-polarized laser-pulse with an overdense plasma and their relation to hole-boring (HB) and ion acceleration. It is demonstrated using particle-in-cell simulations and an analysis of separatrices in single-electron phase-space, that ion motion can suppress fast electron escape to the vacuum, which would otherwise lead to transition to the relativistic transparency regime. A simple analytical estimate shows that for large laser pulse amplitude a 0 the time scale over which ion motion becomes important is much shorter than usually anticipated. As a result of enhanced ion mobility, the threshold density above which HB occurs decreases with the charge-to-mass ratio. Moreover, the transition threshold is seen to depend on the laser temporal profile, due to the effect that the latter has on electron heating. Finally, we report a new regime in which a transition from relativistic transparency to HB occurs dynamically during the course of the interaction. It is shown that, for a fixed laser intensity, this dynamic transition regime allows optimal ion acceleration in terms of both energy and energy spread.